PREVENtion of HeartMate II Pump Thrombosis Through Clinical Management: The PREVENT multi-center study - Maltais, Simon; Kilic, Ahmet; Nathan, Sriram; Keebler, Mary; Emani, Sitaramesh; Ransom, John; Katz, Jason N; Sheridan, Brett; Brieke, Andreas; Egnaczyk, Gregory; Entwistle, 3rd, John W; Adamson, Robert; et al. (The Journal of heart and lung transplantation, 2017)
Recommended structured clinical practices including implant technique, anti-coagulation strategy, and pump speed management (PREVENT [PREVENtion of HeartMate II Pump Thrombosis Through Clinical Management] recommendations) were developed to address risk of early (<3 months) pump thrombosis (PT) risk with HeartMate II (HMII; St. Jude Medical, Inc. [Thoratec Corporation], Pleasanton, CA). We prospectively assessed the HMII PT rate in the current era when participating centers adhered to the PREVENT recommendations. PREVENT was a prospective, multi-center, single-arm, non-randomized study of 300 patients implanted with HMII at 24 participating sites. Confirmed PT (any suspected PT confirmed visually and/or adjudicated by an independent assessor) was evaluated at 3 months (primary end-point) and at 6 months after implantation. The population included 83% men (age 57 years ± 13), 78% destination therapy, and 83% Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) Profile 1-3. Primary end-point analysis showed a confirmed PT of 2.9% at 3 months and 4.8% at 6 months. Adherence to key recommendations included 78% to surgical recommendations, 95% to heparin bridging, and 79% to pump speeds ≥9,000 RPMs (92% >8,600 RPMs). Full adherence to implant techniques, heparin bridging, and pump speeds ≥9,000 RPMs resulted in a significantly lower risk of PT (1.9% vs 8.9%; p < 0.01) and lower composite risk of suspected thrombosis, hemolysis, and ischemic stroke (5.7% vs 17.7%; p < 0.01) at 6 months. Adoption of all components of a structured surgical implant technique and clinical management strategy (PREVENT recommendations) is associated with low rates of confirmed PT.